New organisational strategies in acute coronary syndrome management - L. S. Barbarash; O. V. Kovalenko; V. Yu. Kheraskov; G. V. Moiseenkov; D. V. Kruchkov; G. V. Artamonova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To assess the effectiveness of the new clinical and organisational strategies for specialised treatment of patients with acute coronary syndrome (ACS) — residents of a large industrial city. Material and methods. The object of the study was the system of specialised medical treatment of ACS patients in Kemerovo City. The study venue was the Kuznetsk Basin Cardiology Centre. The study period was 2004-2008, with 16752 ACS patients included. Results. Over the study period, the rates of urgent endovascular interventions increased by 16,8 times. The average time from admission to percutaneous coronary intervention decreased from 95 to 60 minutes. The inconsistencies in ACS diagnosis were registered in less than 9 % of the hospitalised patients. In-hospital case fatality among myocardial infarction patients decreased from 11,1 % to 9,7 % (р≤0,05). Conclusion. The adequate ACS management requires early admission of the patients with possible ACS to a specialised hospital; urgent cardiosurgery interventions in ACS individuals; and multi-level, risk-stratified strategies of invasive and conservative treatment, starting from the moment of admission to the specialised hospital.